Stress Characteristics near Wellbore and Prevention Casing Deformation for Fracturing Horizontal Wells. (30th December 2022) - Zhang, Peng; Wu, Zhenghua; Hu, Shuying; Wei, Jikai; Zhang, Manlai; Ye, Zhengqin; Pu, Chunsheng; Pu, Jingyang
Abstract : Aiming at the problem that casing deformation can easily occur in tight oil horizontal well fracturing, based on the rock mechanics experiments and probability statistics, the distribution characteristics and law of the near-wellbore stress field of the reservoir in STH M56 were solved and analyzed by using the finite element modeling numerical method. The research shows that (1) the max/min horizontal stress ratio of the M56 tight oil reservoir is 1.2, the difference is less than 8 MPa, and this characteristic condition is more conducive to the formation of complex fracturing network in the reservoir during fracturing. (2) In M56, the Mises stress isoline near the borehole is symmetrically distributed. Stress concentration has four dangerous points (30°, 150°, 210° and 330°); a sector-shaped high dangerous stress zone is formed along the four dangerous points. As the pumping pressure increases, the vertical Mises stress first increases and then decreases, while the horizontal Mises stress first decreases and then increases. The max-Mises stress at the casing wall is linearly and positively correlated with the stress uniformity coefficient. When the pumping pressure is 80 MPa, the Mises stress exceeds the safe pressure limit of the casing. A pumping pressure of 70 MPa fracturing is the safe pumping pressure for the reservoir casing. (3) It is found that the 90° and 270° horizontal fixed plane perforations can avoid the dangerous stress zone, increasing and decreasing the injection flow rate of the fracturing pump step by step (step pressure ≤ 5 MPa ) at the start and stop stages of fracturing; the control of the pump pressure during the whole process of fracturing is within 70 MPa, which can prevent the casing deformation.